The additional thermal effect of main tube with BRDF surface in space solar telescope. (5th July 2018) - Li, Rong; Wang, Sen; Wu, Mingchang; Chen, Zhiping; Zhang, Juyong; Lin, Wei
Highlights: BRDF characteristics of MT are proposed to improve TS integrated performance of SST. Six factors of micro-facets in MT are used to represent its BRDF characteristics. A numerical model is developed to predict thermal property of BRDF characteristics. Six series of micro-facets models are constructed with a same thermal scheme. Additional thermal effects of H c, D c, H b, D b, δ and θ are investigated. Abstract: The absorbance, scattering and reflectance characteristics of main tube (MT) surface are critical elements in thermal scheme and scattering suppression of large aperture & small field of view (LASFOV) solar telescopes. With application of Space Solar Telescope (SST), surface of MT with bidirectional reflectance distribution function (BRDF) characteristics can cause additional thermal effect on the primary mirror (PM), field stop (FS) and MT, based on SST scattering elimination scheme. Considering space environment with solar radiation and heat conduction, micro-facets are added on MT to represent its BRDF characteristics, and the homeostatic thermal models of MT are developed with micro-facets to investigate their additional thermal effect. In practical, six series of MT with different micro-facets (height H c and H b, distance D c and D b, angle δ and θ ) are developed to estimate the temperature distribution of SST with thermal analysis software. Thermal analysis shows six parameters representing BRDF characteristics have obvious additional thermal effect on temperature distribution of PM, FS and MT. Therefore, thermal-scattering (TS) integrated design of MT surface with BRDF characteristics is practical and worthy for critical surfaces to obtain ideal TS performance. It is a guidance to optimize critical surfaces in LASFOV solar telescopes to minimizing theirs thermal characteristics and scattering characteristics.